Pengaruh Inkubasi Tepung Cangkang Lokan (TCL) terhadap pH, Kelembaban dan Suhu Tanah Gambut - Aminah, Siti; Weihan, Rayhan Amadius; Putra, Iwandikasyah; Afrillah, Muhammad; Fajri, Maulidil (Jurnal Agrotek Lestari, 2024)
Peatlands have significant potential for development in improving the yields of crop cultivation. Peat soil faces issues of nutrient deficiency and low pH, which pose challenges for cultivation. The application of agricultural lime to acidic soils can increase soil pH. This study aims to examine changes in peat soil pH through the application of various doses of Clam Shell Flour (TCL) as an alternative to lime. The research was conducted at the Teuku Umar University Experimental Field from March to May 2023. The study was designed using a Randomized Block Design with a Non-Factorial approach with 3 dose levels (0 ton/ha, 1 ton/ha, and 2 ton/ha) and consisted of 3 replications. The results of the ANOVA test for peat soil pH during the incubation of ameliorant materials used in this study over 5 weeks showed that Clam Shell Flour (TCL) had no significant effect on pH improvement. Fluctuating changes in peat soil pH were observed in each treatment every week. The lowest pH change range was found in the TCL0 treatment (TCL 0 ton/ha), while the highest was in the TCL1 treatment (TCL 1 ton/ha). Keywords: Peat, Liming, pH, Incubation, Clam Shell Flour